El agente encubierto como medio de investigación de la delincuencia organizada en la Ley de Enjuiciamiento Criminal española - del Pozo Pérez, Marta (2023)
The secret agent’s category has been justified by the need of investigations into international and organized criminal networks. It is polemical but necessary. In lots of cases, without it, could not be possible to get to the bottom of the ins and outs of the organized gangs that we are analyzing. This category should have great future whit the European Union States ́ legal international cooperation in the development, both, of the future European Constitution and of the Judicial Assistance Agreement now in rule.